Kağıt makinesinin bilgisayarla kontrolü - Vurgun, Bülent (Fen Bilimleri Enstitüsü, 1993)
Kağıt günümüzün popüler ürünlerindendir. özellikle kurulan arıtma tesislerinden sonra çevresel kriterlerle çatışmaması ve yeniden üretime sokulabilmesi bugün hemen hemen her sahada kullanılması sonucunu doğurmuştur. Kağıt üretimi kaynakların sürekli hareketini gerektiren ve dar toleranslar içinde çalışılan zor bir prosestir. Prosese giren kaynakların türü ve miktarı, üretim aşamaları üretilen ürünün cinsine göre çok farklılıklar içerebilmektedir. Bu açıdan 1. bölümde kağıt sanayinin, tarihsel gelişmesini de aktaracak şekilde, tanıtılması uygun görülmüştür. Ayrıca yine bu bölümde çevresel kriterler açısından bu sanayinin özeleştirisi ve yakın gelecekteki muhtemel konumu incelenmiştir. ikinci bölümde sistemi oluşturan modüllerin önce genel dağılımı verilmiş ve daha sonra sistemi oluşturan alt modeller ayrı ayrı tanıtılmıştır. Modüller arası ilişkiler gerek şemalarla ve gerekse sayısal olarak belirtilmiş ve sistemin dinamik davranışının incelenme sine çalışılmıştır. Üçüncü bölümde modern kağıt makineleri için artık kaçınılmaz bir konumda olan on-line temel ağırlık, nem, kül, kalınlık vb. gibi algılayıcılar ve bunların ölçü sistemleri tanıtılmış; sürekli ve hassas ölçüm için güvenilirlikleri tartışılmıştır. Dördüncü bölümde sistemin analitik modelinin kullanıldığı ve pratik gerçeklenmiş bir kontrol yapısı örnek olarak incelenmiştir. Bu yapı Honeywell firması tarafından geliştirilen ve TDC 3000 DCS sistemlerinde kullandıkları HMPC (yatay çokdeğişkenli tahmini kontrol) kontrol sistemidir.

Trend to increase production rate in addition to the high quality demands have emphasized the requirements for paper machine's stability. The overall goal of this thesis is to develop the paper making process and its control system to optimally produce of most uniform quality. The major most important aim of this thesis is to develop whole mathematical model of paper machine; included explanation of sub models. Also pressure, flow and concentration (fiber, filler, and fines) dynamics will be discussed. The second subgoal is to study new sensors on continuous on-line measurement, in particular their reliability, error compensation, and use ability for control applications. The third is to represents and explain paper making process from wood to paper. Also one newly developed predictive based control strategy ( HMPC - Horizon Multivariable Predictive Control} will be explained. Paper is fantastic material and the usage has; since the first handmade papers were produced by the Chinese almost 2000 year ago, gradually become more and more sophisticated, complicated, and smart, through knowledge. This evolution will continue in the years ahead too. Slightly more than 150 years ago the first paper mill was put into operation. Some years after, in 1874, the first pulp (sulfite) mill was built in Bergvik, Sweden. Since then development of paper making processes have been tremendous : 1. It has become possible to utilize new types of fibers 2. Knowledge of fibers and the pulping processes has increased enormously as has the knowledge of how to use different fibers in different grades. VII 3. Production capacity of paper line has increased more than hundred fold. 4. Completely new chemicals have appeared; the chemicals used are recycled and the system have become more and more closed. During the next 100 years the development of paper processes will surely continue. This thesis may address today as a reference, and some possible development trends during the next 10-20 years. An overall approach should be applied to evaluation of the environmental characteristics of products. Pulp and paper products satisfy virtually all environmental criteria for manufactured products. Paper is made of a natural raw material that is a renewable resource. Production can give rise to environmental problems, but environmental protection measures led to greatly reduced emissions after treatment systems occurred. Paper is useful to use and can be re-used to a large extend as a source of fibers. It can also be incinerated to produce energy and thereby to conserve finite fossil fuels and reduce pollution they cause. The carbon dioxide given off during the incineration of paper is incor- pareted into newly growing trees through photosynthesis. Paper is therefore a biofuel which does not contribute to the green-house effect. Forest Resources : The total area of forests in the world is estimated to be closed to 2.8 billion hectares out of which hardwood forests account for 60 % and softwood for 40 %. About 18 million hectares of this area consists of industrial fast-growing plantations. Overall annual industrial wood consumption is about 1.5 billion m.3. One third of this is consumed by the pulp and paper industry. Total world consumption paper and board in 1991 amounts to almost 250 million tones. Today, we would expect an even greater consumption increase particularly in Asia. The proportion of total pulp supply from recycled fibers is rapidly increasing. At the end of this century, the total demand of recycled is average percentage of about 40 %. VIII All paper producers have to fulfill three requirements- environment, quality, and economy (or profitability}. At the same time the reference, or criterion changes gradually. The environmental issue has been so strong as well as economic factors and have sometimes be enforced to somewhat lower priority levels. Paper Machine : Paper machine consists of following sub processes : Piping, a wire pit, centrifugal cleaners, a deaeration tank, screens, a head box, wire section, press section, dryer section including coating, and a callender section. The centrifugal cleaners are used to separate sand, shivers, fiber, bundles and other impurities from the pulp stock:. A vacuum exists in the deaeration tank corresponding to about the boiling point of water at the temperature of the stock. As the stock sprayed into the tank, it forms droplets and boils in the vacuum. The amount of both free and bound air is decreased, and this improves dewatering on the wire section and sheet formation. The headbox is a very important part of the wet end as it largely determines the basis weight uniformity through keeping the amount of the flow steady to wire section both in cross and machine direction. The wire section (fourdrinier) removes main part of the water used to transport fiber, filler, fines, and additives to press section. A part amount of fiber, filler, fines, and additives goes through the wire. Mechanical filtration and colloidal forces try to keep particles on wire under great hydrodynamic forces. This mechanism İ3 called retention. The water from wire section used for dilution is called white water. The purpose of the wire pit is to collect flows from wet end to be used for dilution of heavy stock in the bottom of wire pit to the consistency 0.05 % - 1 %. The paper machine's press section removes as much water as possible from the web. Because removing water by pressing is considerably cheaper than using steam in the drier section. State of the art paper machines have three or four press sections. At press section the system looks after pressures and roll movements, make IX sure that the felts stay in place and are properly tensioned. At the drier section water is removed from the web by means of steam. The drier section usually consists of 6-12 drier cylinders in two rows on top of one another. In addition, cylinders in drier section divided into steam groups. System controls the steam pressure in these groups so that temperatures suitable for drying paper are achieved. The system sees to it that the pressure difference between the steam and condense and the various steam groups is as desired. This is mo3t importance in order that the condansate be discharged from the drier cylinders in the desired manner and that recycling of the steam can be kept under control. An integrated process and quality control system, control paper moisture by regulating the various drier group s steam pressure or other dries. The machine callender improves the smoothness and glossiness of paper. It is also used to control thickness. The thickness profile can be slightly rectified by zone pressures. Modular Analysis of Paper Machine : Thİ3 part contains a description of the mathematical models used in each of the modules in general diagram of paper machine, (figure 2.4 & figure 2.5) The descriptions are written in the format of a technical paper. Typical engineering nomenclature (e.g. T for temperature) is used to describe the models. Process modules can be divided into two categories - general purpose and paper mill. General purpose modules are used to represent processes occurring in several subsystems in an integrated mill. These modules include a splitter, mixer, pump, valve, heat exchangers, separators and flow controllers.
Computer aided control of paper machine
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Keywords: Bilgisayar destekli denetim; Kağıt; Makine; Computer aided control; Paper; Machinery